THE PREVALENCE OF (OMPA, CSUE) GENES AMONG BIOFILM PRODUCER ACINETOBACTER BAUMANNII ISOLATES - Noor Alhuda A. K; S. S Mahmood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
Acinetobacter baumannii is a significant public health problem because it is capable of forming biofilms that may be responsible for the survival of this pathogen in the hospital environment. The aim of this study is to determine the role of (OmpA, CsuE) genes in biofilm production among A. baumannii isolates. A total of 100 clinical isolates of bacteria were collected from a different sources.  All isolates were identified by biochemical test, specific selective media (CHROMagar) and polymerase chain reaction by detection presence of (blaOXA51) gene. only 60 isolates were diagnosed as A. baumannii, and to determine the biofilm production capacity two different methods were used Congo red agar method(CRA) and Microtiter plate method (MTP). MTP method result showed 85% of isolates were able to form biofilms, on the other hand, 33.33% of isolates had a biofilm production ability by showing bright black colonies on CRA. Conventional PCR was used to detect the presence of (OmpA, CsuE) genes and the result showed the prevalence of both genes in all isolates were 97%(58/60). It also shows a strong correlation between the presence of these genes and biofilm formation.